Estrategias didácticas y su incidencia en el proceso de aprendizaje de los estudiantes con dislexia de la Escuela de Educación Básica Juan E. Verdesoto, Babahoyo, 2022-2023 - Tamayo Flores, Daniela Alejandrina (2023)
Teaching strategies are those pedagogical activities that have the purpose of facilitating the learning process. Through these strategies, students have the opportunity to conceive new knowledge in a meaningful way. For this reason, the main objective of this research is to determine the incidence of teaching strategies in the learning process of students with dyslexia at the Juan E. Verdesoto School of Basic Education, 2022-2023. The methodology used in the case study conforms to a qualitative approach; While the research was descriptive, field and explanatory, inductive and deductive methods were also used, the population and sample are represented by 2 students with dyslexia and the tutor teacher of the 4th parallel year "B" belonging to the School of Basic Education Juan E. Verdesoto, it is important to mention that to obtain relevant information on the topic, two techniques were used: direct observation, aimed at dyslexic students, and an interview with the teacher was also used. The results obtained were that the educator does not apply innovative teaching strategies that respond to the needs of students with dyslexia, these strategies do not adequately address the reading and writing difficulties of students with dyslexia, this can lead to a lack of progress in the acquisition of reading and writing skills.